Infectious Diseases Physician Compensation: An Improved Perspective. (27th April 2016) - Ritter, Jethro Trees; Lynch, John B.; MacIntyre, Ann T.; Trotman, Robin
Abstract : National physician compensation surveys (e.g. MGMA, Medscape) may not accurately reflect the income potential of infectious diseases specialists, due to small sample sizes. The authors report the findings of a compensation survey undertaken by the Infectious Diseases Society of America. Abstract: Negotiating physician compensation can be complicated because many factors now influence the ways in which physicians can be compensated. Infectious diseases (ID) specialists typically provide a wide array of services, ranging from patient care to administrative leadership. Compensation surveys from national organizations have produced results based on small samples and often are not congruent with ID physicians' perceptions. In July of 2015, the Infectious Diseases Society of America (IDSA) conducted a compensation survey to assess current compensation earned by the diverse ID specialists within its membership. Members of IDSA's Clinical Affairs Committee report the results from the 2015 IDSA Physician Compensation survey, with a particular focus on the findings from respondents who indicate "patient care" as their primary responsibility and present a discussion that compares and contrasts results against other survey data.